An Analysis of Code-Switching Among Students of the Malaysia Japan Higher Education Programme) (Jurnal Bahasa, 2025)
Code-switching is a common phenomenon in foreign language learning. However, excessive and uncontrolled code-switching can disrupt the learning process and cause learners to become confused when acquiring the structural features of the target language. Therefore, this study was conducted to identify the languages used alongside Japanese, analyse the types of code-switching based on Poplack’s (1980) framework which classifies code-switching into three main categories, namely tag, intrasentential, and intersentential, and determine the functions of code-switching based on Olcay’s (2005) classification. This study involved 73 respondents from the Malaysia-Japan Higher Education Programme, and the data used were in the form of recordings. The findings reveal that all three types of code switching (tag, intrasentential, and intersentential) were found in the respondents’ utterances. In terms of functions, only four out of the seven code-switching functions were identified, namely the affective function, the turn-holding function, the conflict-control function, and the topic-shift function. The study also found that code-switching among students learning Japanese involved English and Malay, with intrasentential code-switching recording the highest frequency. Through this study, the researchers were able to relate the social functions to the code-switching that occurs in foreign language learning.Keywords: Code-switching, tags, intrasentential, intersentential, Malay language, Japanese languageFull text: PDF